Aspek Lingual Tegursapa Sosial Masyarakat Jawa Kota Semarang - Suryadi, M (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
AbstractThe purpose of this study is to describe lingual aspects that strengthen the speech of the clergy of Java Coastal community in Semarang City. This greeting remarks as a glue of the socioal harmony and horizontal conflict absorbers, as well as a feature of uniqueness in the connection of social intimacy in the coastal region.Research location in Semarang City. Selection of respondents and informants using purposive sampling system. Data collection methods were conducted through structured interviews, in-depth interviews, and focus group discs. The method of data analysis using the separation of components on speech by greeting sad lingual aspects contained in the speech.There are three lingual aspects that influence the power of speech:  speech sauce, variety, and formIntisariTujuan penelitian ini adalah mendeskripsikan aspek lingual yang memperkuat tuturan tegur-sapa social masyarakat Jawa Pesisir di Kota Semarang.  Tuturan bertegur-sapa ini sebagai perekat harmoni sosioal dan peredam konflik horizontal, sekaligus sebagai fitur keunikan dalam pertalian keakraban sosial di wilayah pesisiran.  Lokasi penelitian di Kota Semarang. Pemilihan responden dan informan menggunakan sistem purposive sampling. Metode pengumpulan data dilakukan melalui wawancara terstruktur, wawancara  mendalam, dan focus group discus.Metode analisis data menggunakan pemilahan komponen pada tuturan bertegur-sapa melalui aspek-aspek lingual yang terdapat pada tuturan. Ditemukan tiga aspek lingual yang mempengaruhi kekuatan tuturan bertegur sapa social, yakni kecap ujaran,ragam, dan bentuk.